Effect of biotransformation by liver S9 enzymes on the mutagenicity and cytotoxicity of melanin extracted from Aspergillus nidulans - Gonçalves, Rita de Cássia Ribeiro; Kitagawa, Rodrigo Rezende; Varanda, Eliana Aparecida [UNESP]; Raddi, Maria Stella Gonçalves [UNESP]; Leite, Carla Andrea [UNESP]; Sponchiado, Sandra Regina Pombeiro [UNESP] (Taylor & Francis, 2015)
A mutant that exhibited increased melanin pigment production was isolated from Aspergillus nidulans fungus. This pigment has aroused biotechnological interest due to its photoprotector and antioxidant properties. In a recent study, we showed that melanin from A. nidulans also inhibits NO and TNF-α production. The present study evaluates the mutagenicity and cytotoxicity of melanin extracted from A. nidulans after its exposure to liver S9 enzymes. The cytotoxicity of multiple concentrations of melanin (31.2-500 μg/mL) against the McCoy cell line was evaluated using the Neutral Red assay, after incubation for 24 h. Mutagenicity was assessed using the Ames test with the Salmonella typhimurium strains TA98, TA97a, TA100, and TA102 at concentrations ranging from 125 μg/plate to 1 mg/plate after incubation for 48 h. The cytotoxicity of A. nidulans melanin after incubation with S9 enzymes was less than (CI50 value= 413.4 ± 3.1 μg/mL) that of other toxins, such as cyclophosphamide (CI50 value = 15 ± 1.2 μg/mL), suggesting that even the metabolised pigment does not cause significant damage to cellular components at concentrations up to 100 μg/mL. In addition, melanin did not exhibit mutagenic properties against the TA 97a, TA 98, TA 100, or TA 102 strains of S. typhimurium, as shown by a mutagenic index (MI)  <2 in all assays. The significance of these results supports the use of melanin as a therapeutic reagent because it possesses low cytotoxicity and mutagenic potential, even when processed through an external metabolising system.
Keywords: Cytotoxic; Fungi; Mutagenic; Pigment